Personality principle of the penalty and penal execution (Revista do Tribunal Regional Federal da 3ª Região, 2017)
The principle of the personality of the penalty (art. 5, XLV, of the Federal Constitution), as well as the principle of legality, humanity and individualization of the penalty, represents a great achievement in criminal law. After all, from the point of view of the purposes of the penalty - and even for reasons of justice - there is no reason to apply a reprimand to someone who did not contribute to the commission of the crime. Despite its importance, the principle is often disregarded or misinterpreted, generating misplaced discussions about its meaning and scope. On the other hand, little is written about its impact in the specific context of penal execution. It should not be forgotten, however, that during the execution of the sentence - while in a closed regime, for example - the individual needs the effective application of penal principles just as much as during the trial. In Brazilian law, some of the main issues involving the personality of the sentence arise precisely at the time of execution. This is because, fortunately, our criminal legislation no longer provides for the punishment of children and grandchildren for crimes committed by their parents and grandparents. Nowadays, it is more common for the sanction to harm third parties reflexively, and this occurs above all during its enforcement. It is therefore worth examining this principle in order to determine its scope and the extent to which it is being observed, as well as the instruments available in our legislation to mitigate the damage that the application of the penalty causes to third parties.
Keywords: principle of the personality of the penalty; criminal enforcement; custodial sentence; restrictive sentence of rights